ANTITHROMBOTIC PROPHYLAXIS REPEATED PREECLAMPSIA IN PATIENTS WITH THROMBOPHILIA - E. V. Zhuravleva (IRBIS LLC, 2016)
Objective. To evaluate the efficiency of antithrombotic therapy to prevent repeated preeclampsia in patients with thrombophilia. Subject and methods. A prospective clinical study was conducted 66 patients with thrombophilia (genetic, acquired or concomitant) and with history of preeclampsia: 35 patients addressed and were followed since fertile cycle (subgroup Ia) and 31 patients addressed during pregnancy and were followed since 6-13 weeks of gestation - IIa subgroup. Control group - 50 patients without both obstetrics and gynecology and thrombotic complications in history. Therapy included LMWG (klexan), B vitamins, antioxidants and micronized progesterone. Results. The all period of pregnancy, obstetric and perinatal outcomes were better in patients receiving therapy since fertile cycle compared with group of patients whose therapy was initiated during pregnancy.Conclusion. To prevent re-PE at a subsequent pregnancy, the therapy should be start since fertile cycle, continuing during pregnancy, childbirth and the postpartum period. Therapy should include LMWH, B vitamins, antioxidants and micronized progesterone.